"madone De Bentalha"قراءة سيميو-أنثروبولوجية لصورة - سكومي, فاطيمة (جامعة الوادي - University of Eloued, 2023)
الملخص يروم هذا المقال تقديم قراءة سيميو-أنثروبولوجية لإحدى الصور الفوتوغرافية التي جالت العالم وتخطت الزمان والمكان الذي وجدت فيه، لتصبح "أيقونة"، "مقدسة" و"أسطورة"، صورة اثارت الرأي العام الغربي خاصة وأسالت الكثير من الحبر بفضل العلامات والرموز التي أوحت بها والحيز الاعلامي الذي شغلته، انها صورة التي التقطت عقب مجزرة "بن طلحة" سنة 1997، فقد نابت عن الآلاف من الكتابات والمئات من الصور لتعطي وجها لـ"المأساة الجزائرية"، فما قصتها وما هي الحمولة الدلالية التي ساهمت في انتشارها وشهرتها الكبيرة خاصة في العالم المسيحي، هذا ما سيحاول هذا المقال مقاربته من خلال قراءات متعددة للصورة. Abstract: This article aims to present a semio-anthropological reading of one of the photographs that has traveled around the world and transcended the time and place in which it was formed, to become an “icon”, “sacred” and “legend”, an image that stirred occidental public opinion in particular and sparked a lot of ink because of the signs and symbols it inspired and the media space that occupied it, it is the picture of (Madone de Bentalha) that was taken after the "Bentalha" massacre in 1997, as it sprouted from thousands of writings and hundreds of pictures to give a face to the "Algerian tragedy", so what is its story and what are the indications that contributedo its spread and great fame, especially in the Christian world:?, This is what this article will try to approach through multiple readings of the picture.
مقال
Keywords: Semiotics, Anthropologycal, Bentalha, Photo, Christian iconography, the Virgin; سيمائية,أنتروبولجية,بن طلحة,صورة فوتوغرافية,أيقونة مسيحية,العذراء